MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI METODE GLENN DOMAN BAGI ANAK TUNAGRAHITA SEDANG - Desi Sumarlin, Tarmansyah, Yarmis Hasan (Universitas Negeri Padang, 2013)
The research was motivated by mental retardation children are not familiar in consonants and vowely [u]. This study aims to see if the Glenn Doman method can be applied to improve the reading ability for mental retardation childrend. This research uses experimental research in the form of Single Subject Research (SSR) with the AB design. The object of this research is a mental retardation childrend (X) in firts grade. The target behavior in this study is the child's ability to read body member and a member of the family, is the assessment given taskbar every correct answer on data’s format. This research was first seen from the baseline condition in the child's reading ability-rich earlier. This was followed in the intervention condition who continued to be treated. The data obtained were processed with graphs. So the results of this study can be clearly defined. The data is analyzed and obtained the following results. on the baseline condition child only can read one word that “papa”. At the intervention condition were studying with Glenn Doman method children can read all the words correctly. In the first day of interventions, the child can read four words, in the second and third day the child is able to read five words correctly, on the fourth day the child is able to read eight words correctly, on the fifth, sixth, seventh, and eighth the child is able to read all the words correctly, and the word is:” mama, papa, kakak, adik, nenek, mata, hidung, mulut, telinga, dan rambut”. It means that learning to use Glenn Doman method can be applied to improve the reading ability of the mental retardation childrend. Teachers and researchers suggest further research in order to provide learning by using Glenn Doman method to improve reading skills beginning in the next lesson.